Rancang Bangun Purwarupa Pendeteksi Berat Muatan Bus Transjakarta Menggunakan Metode Incremental Berbasis Mikrokontroler Arduino Uno - Yudi Irawan Chandra; Kosdiana Kosdiana (Informatika Universitas Siliwangi, 2020)
At present transportation is a common thing for the citizens of the City of Jakarta. Handling by the Jakarta City government continues to be pursued. One way to do this is to build a busway lane. The construction of this route is expected to overcome the problem of congestion in the city of Jakarta. However, all of that can make many people use Transjakarta transportation during working hours, so that there will be overload and threaten the feasibility of Transjakarta transportation.An incremental model is a system development model in software engineering based on software requirements that are broken down into functions or parts so that the development model is phased in. on the other hand there is interpreting the incremental model as an improvement of the waterfall model and as a standard topdown approach. Using this model is expected to produce software that functions quickly and earlier during the software life cycle, is more flexible and cheaper to change the scope and requirements, thereby reducing initial shipping costs. Furthermore this model is easier to do testing and debug during smaller iterations.The development of life and technology at this time is felt more quickly and demands change in various sectors. Very rapid technological advances allow for various businesses to provide convenience and comfort for humans. One effort to provide convenience and comfort is through the development of load weight detection system design on Transjakarta buses. Adding Arduino as a